Could Broccoli and Cauliflower Influence the Dispersal Dynamics of Western Flower Thrips (Thysanoptera: Thripidae) to Lettuce in the Salinas Valley of California?. Issue 4 (6th June 2021) - Joseph, Shimat V; Koike, Steven T
Abstract: The western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is an important, worldwide vector of two tospoviruses (Family Bunyaviridae; Genus Tospovirus ), Impatiens necrotic spot virus (INSV) and Tomato spotted wilt virus (TSWV). In the Salinas Valley of California, INSV causes severe necrosis, stunting, and crop losses to lettuce ( Lactuca sativa L.). Because broccoli ( Brassica oleracea var. italica L.) and cauliflower ( Brassica oleracea var. botrytis L.) are major rotation crops with lettuce in the Salinas Valley, it is critical to understand if these Brassicas influence the dispersal dynamics of F. occidentalis . In 2013 and 2014, surveys were conducted evaluating yellow sticky cards and plant samples in lettuce, broccoli, and cauliflower fields in three regions of the Salinas Valley. F. occidentalis were collected on sticky cards from April to November and on foliage in all three regions. Two-choice oviposition assays as well as no-choice and two-choice feeding assays were conducted where F. occidentalis adults were exposed to leaves of lettuce, broccoli, and cauliflower. A significantly greater number of eggs was found on lettuce than on broccoli or cauliflower leaves in the choice assay, whereas for the broccoli and cauliflower choice assay, the number of eggs retrieved was low and not significantly different between hosts. The number of F. occidentalis feeding spots and leaf area injury ratings were similar on broccoli and lettuce leaves but were significantly lower on cauliflower than on lettuce and broccoli leaves. The implications of these results on thrips and plant virus management are discussed.